The Role of Macrophages in Tumor Development - Gerben J. van der Bij; Steven J. Oosterling; Sybren Meijer; Robert H. J. Beelen; Marjolein van Egmond (Cellular Oncology)
Macrophages constitute a large proportion of the immune cell infiltrate, which is present in many tumors. Activation state of macrophages is greatly influenced by their environment, leading to different macrophage subsets with diverse functions. Although previously regarded as potent immune cells that are capable of destroying tumor cells, recent literature focuses on the ability of macrophages to promote tumor development due to secretion of mediators, like growth and angiogenic factors. It is now becoming increasingly clear that a complicated synergistic relationship exists between macrophages and malignant cells whereby tumor cells can affect macrophage phenotype, and vice versa. As such, macrophages and their contribution in cancer development are currently subject of debate.